(untitled) (New York, 2002)
Highly respected poets, Hall and Emblem have chosen classical and contemporary selections to make this a delightful writer's companion, now in it's ninth edition. A Writer's Reader is a collection of essays, short stories, and poems organized alphabetically by author. Several readings by the same author are provided for a closer look at a writer's style. A rhetorical and thematic index is included to allow readers a way of cross-referencing selections
Keywords: College readers,Đọc giả trung học,English language,Tiếng Anh; Rhetoric,Tu từ học